MENINGKATKAN KETERAMPILAN MEMBUAT VAS BUNGA GELAS DARI KERTAS KORAN MELALUI BANTUAN METODE DEMONTRASI BAGI ANAK TUNARUNGU KELAS III DI SDLB PAINAN - Hayati - Putri (Universitas Negeri Padang, 2013)
This study removed using action research method (Classroom Action Research) conducted in collaboration with colleagues. Data collected through observation techniques, and tests, and then analyzed qualitatively andquantitatively The results showed that peer assistance in making a flower pot through two cycles. Each Five meetings were held for the first cycle and four for the second cycle that began with the beginning, the core activities and the final activity showed good success. The assessment (initial test) the ability of Cycle I AL gets results (73,3%), TT (87,0%), and SS got value (33.3%). In the second cycle AL scored (87,0%), TT got (94%), and NS mndapat value (80%) This shows the increase and success after extensive repairs, and the role of peers in helping make the a flower pot. Maka suggested to teachers in teaching skills to children tunarungu Lightweight better students who are able / completion to help a friend who has not completed (peer tutoring), so that children are able to independently light tunarungu either within the family or within the community, and can live well with good economy thanks to possess skills that can ensure their future.